Pengaruh Disiplin Kerja Dan Motivasi Terhadap Kinerja Dosen FEB Universitas Muhammadiyah Lamongan - Abdul Majid; Indah Lokahita Safitri; Indri Puji Astuti; Muhammad Miko Firdaus; Moch. Arif Syafi’i; Sri Yaumi (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2023)
The purpose of this study was to determine the effect of work discipline and motivation on the performance of FEB lecturers at Muhammadiyah Lamongan University. Associative research is the type used in this study. The population and sample of this study were all FEB lecturers at Muhammadiyah Lamongan University, the data collection technique used a questionnaire. The data analysis technique uses multiple linear regression tests. The results showed that work discipline had no effect on lecturer performance and motivation had an effect on the performance of FEB lecturers at Muhammadiyah Lamongan University.